Characterization and Development of Rapimelt Tablet for Anti Hypertensive Management. - Varma, Mandapati Sreenivas; Singh, Surendra Pratap; Malik, Jitendra Kumar; Kumar Shah, Sunil (Journal of Neonatal Surgery, 2025)
Rapimelt Tablets of Treprostinil Diolamine (TD) optimized by successfully prepared by direct compression method using selected superdisintegrants with Crosspovidone 1.5%, 3%, 6%, Crosscarmellose 1.5%, 3%, 6% and Sodium starch glycolate 1.5%, 3%, 6%, for the better patient compliance and effective therapy the relative efficiency of these superdisintegrant to improve the disintegration and dissolution rate of tablets were found in order. The disintegration of TF1, TF2, TF3 formulations to be as 8, 6, 5secs respectively and is almost better than TF4, TF5, TF6, TF7, TF8, TF9 formulations. Formulation TF3 In-vitro Dissolution studie 10 minutes almost total amount of the drug is released 6% crosspovidone (i.e. 96.96%). Crosspovidone shows good result as compare to other superdisintegrants.The drug release profiles of TD rapimelt tablets were fitted to various kinetic models such as Zero order, First order, Higuchi, Peppas and Hixson-Crowell. The dissolution parameters such as dissolution efficiency (DE) at 10 and 30 minutes were increased proportionately. Half-life of drug i.e., T50 was found to be 181,1.70, 1.53, 2.42, 1.94, 1.59, 2.81, 1.98 and 1.73 min for TF1, TF2, TF3, TF4, TF5, TF6, TF7, TF8 and TF9 formulations respectively. Shelf-life of the drug i.e.,T90 was found to be 9.75, 8.75, 8.24, 9.28 and 8.92 minutes for TF1, TF2, TF3, TF5 and TF6 formulations respectively. The drug release patterns of TD rapimelt tablets had followed the first order kinetic model. This release patterns are evident with the correlation coefficient ‘r’ values which are nearer to 1. The optimized formulation TF3 is kept for Accelerated stability stability studies. Studies, the results indicated that there was no significant change in evaluation of the tablets. In-vivo studies of TD rapimelt tablets. TD showed good linear relationship between the under peak areas and the concentrations. The lower limit of quantization was 0.05 mcg/ml for determination of TD in plasma. The limit had been sufficient for PK studies of TD Rapimelt tablets.